Cinética do fluoreto sob diferentes formas após escovação com dentifrício de própolis vermelha brasileira: ensaio clínico randomizado - Girão Júnior, Francisco Josimar (2020)
There are several natural compounds with biological activity that have had their properties and applicability evaluated in Dentistry, among them the Brazilian Red Propolis (BRP), a resinous complex with several biological activities documented in the literature, being o of the most promising natural products, with proven in vitro and in vivo antimicrobial and anti-inflammatory activities. Dental hard tissues undergo continuous demineralization processes followed by remineralization and restoration of dental enamel integrity, a process influenced by several factors such as the presence of saliva, bioavailable fluoride concentration and dental biofilm control. Fluoride dentifrices with antimicrobial properties are increasingly being indicated for dental biofilm control, where incorporation with natural products is an affordable and effective alternative. This study aimed to evaluate the availability of fluoride after use of a toothpaste incorporated with brazilian red propolis (BRP, INPI Patent Number BR1020170110974) and to compare it to a fluoride toothpaste in healthy participants. This study was conducted in a double-blind, randomized, controlled, and crossover design. Following a washout period with non-fluoridated toothpaste for three days, participants brushed with the common fluoride toothpaste, followed by three more washout days and a new brush with the propolis toothpaste. Saliva samples of participants were collected at the times: 0 - baseline and 5, 15, 30, 45 and 60 minutes after brushing with each toothpaste. The samples were electrochemically analyzed for fluoride (ISE) using the method described by Cury and collaborators. Salivary fluoride concentrations per sampling time point were submitted to the Kolmogorov-Smirnov normality test and compared by Wilcoxon and Mann-Whitney tests between both toothpastes. The value of α was set at 0.05 in all cases. Results: Salivary fluoride concentrations showed no statistically significant difference when comparing the two treatments (p> 0.05). After one hour, all available fluoride concentrations in saliva decreased, with no significant difference between BRP and common fluoride dentifrice treatment samples (p> 0.05; two-way ANOVA). The results showed that, after 1 hour of brushing with the different toothpastes, there was no difference between the fluoride concentrations analyzed. Thus, the results of this study suggest that the propolis incorporated in the dentifrice did not interfere in the kinetics and bioavailability of fluoride ion in saliva samples, enabling its integration with the pharmaceutical formula, promoting its anti-inflammatory and antimicrobial benefits without compromising the anti-caries activity of the formulation.